Support area as an indicator of environmental load: Comparison between Embodied Energy, Ecological Footprint, and Emergy Accounting methods - Agostinho, Feni [UNESP]; Pereira, Lucas (Elsevier B.V., 2013)
Environmental aspects have been acknowledged as an important issue in decision making at any field during the last two decades. There are several available methodologies able to assess the environmental burden, among which the Ecological Footprint has been widely used due to its easy-to-understand final indicator. However, its theoretical base has been target of some criticisms about the inadequate representation of the sustainability concept by its final indicator. In a parallel way, efforts have been made to use the theoretical strength of the Emergy Accounting to obtain an index similar to that supplied by the Ecological Footprint. Focusing on these aspects, this work assesses the support area (SA) index for Brazilian sugarcane and American corn crop through four different approaches: Embodied Energy Analysis (SA(EE)), Ecological Footprint (SA(EF)), Renewable Empower Density (SA(R)), and Emergy Net Primary Productivity (SA(NPP)). Results indicate that the load on environment varies accordingly to the methodology considered for its calculation, in which emergy approach showed the higher values. Focusing on crops comparison, the load by producing both crops are similar with an average of 0.04 ha obtained by SA(EE), 1.86 ha by SA(EF), 4.24 ha by SA(R), and 4.32 ha by SA(NPP). Discussion indicates that support area calculated using Emergy Accounting is more eligible to represent the load on the environment due to its global scale view. Nevertheless, each methodology has its contribution depending of the study objectives, but it is important to consider the real meaning and the scope of each one. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Corn; Ecological Footprint; Emergy Accounting; Embodied Energy Analysis; Environmental load; Sugarcane